Y-1=2(x-2/3)

Simple and best practice solution for Y-1=2(x-2/3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for Y-1=2(x-2/3) equation:


x in (-oo:+oo)

Y-1 = 2*(x-(2/3)) // - 2*(x-(2/3))

Y-(2*(x-(2/3)))-1 = 0

Y-2*(x-2/3)-1 = 0

Y-2*(x-2/3)-1 = 0

Y-2*x-1+4/3 = 0

Y-2*x+1/3 = 0

Y-2*x+1/3 = 0

Y-2*x+1/3 = 0 // - Y+1/3

-2*x = -(Y+1/3) // : -2

x = (-(Y+1/3))/(-2)

x = (Y+1/3)/2

x = (Y+1/3)/2

See similar equations:

| 3x-(9x+5)=2x-37 | | 8m-20=12+6m | | 8.4y+9.77=-62.47 | | -21.32=3.2x+3 | | 3b^2-2=25 | | 8t+6-7t=6 | | 4x-30=7x-54 | | 6.6+1.7n=2.52 | | 5(2-4r)-3r=4r-287 | | 1.01(1.27)(9-x)=11 | | 4b=2b-1 | | 5.5y-6.1=19.20 | | b=3/4 | | 24(1.5+3)=n | | 8z(squared)=6z(squared)+38 | | x+27.3=8.9 | | m/-10=12=67 | | (7/10)/(5/16) | | 4x-5+2x+15=130 | | 4(3-5p)=9p-278 | | 2b+3=46-4 | | v^2+7=32 | | 4/9=x/11 | | 1.5+3=24 | | x-19=8x+2 | | -4y-15=-2y+5 | | 38(17-5.5x)=13(5x-9)+23.2 | | 24=1.5+3 | | 168*0.8=134 | | 110=6b+4b | | (x-5)-3=-28 | | 3(9y-2.6)+7.2=6(8y-0.1) |

Equations solver categories